Mechanisms of resistance to methotrexate in childhood acute lymphoblastic leukemia: circumvention of thymidylate synthase inhibition - Weigand, Martina; Frei, Eva; Graf, N.; Buchholz, B.; Wolfrom, C.; Breuer, Andrea; Wießler, Manfred (Journal of cancer research and clinical oncology, 1999)
Purpose: In about 25% of patients suffering from acute lymphoblastic leukemia (ALL) treatment failures occur that are most likely due to development of resistance to methotrexate (MTX). Blasts from patients with ALL were evaluated for MTX uptake, formation of long-chain MTX polyglutamates (MTX-Glu5+6), cytotoxicity and thymidylate synthase inhibition by MTX and compared to blasts from patients with acute myelogenous leukemia (AML). Methods: Radioactively labeled MTX-Glu n were analyzed by means of HPLC. Thymidylate synthase activity was measured by a tritium-release assay. Cytotoxicity was determined by trypan blue exclusion. Results: In most ALL blasts (n = 9) large amounts of MTX-Glu5+6 (1.06-7.03 pmol/107cells) and high cytotoxicity (43.5%-92.7%) were found, while in others small amounts of MTX-Glu5+6 (0.0-0.39 pmol/107cells) caused only weak cytotoxicity (6.0%-27.9%) (n = 5, 2 relapsed patients). Resistance to MTX in blasts from AML patients (n = 5) was also caused by reduced synthesis of MTX-Glu5+6 (0.0-0.42 pmol/107cells). In contrast, some ALL blasts (n = 7, 4 relapsed patients) were able to survive MTX treatment despite large amounts of MTX-Glu5+6 (1.5-5.05 pmol/107cells) and extensive thymidylate synthase inhibition. Conclusions: Since the majority of ALL patients were examined at first diagnosis, an inherent mechanism of resistance seems most likely. We propose a mechanism based on the switch of thymidylate synthesis to the salvage pathway.